Bioaccessibility of phenolic compounds from a wheat beer enriched with alginate-encapsulated wine industry by-product - Anna Carolyna Goulart Vieira; Genilton Alves da Silva; Renata Valeriano Tonon; Gizele Cardoso Fontes Sant’Ana; Maria Helena Miguez da Rocha Leão; Daniel Perrone; Priscilla Filomena Fonseca Amaral (Ciência Rural)
ABSTRACT: Wine industry by-product (WIBP) encapsulated in alginate beads were incorporated to beer to increase antioxidant properties. The phenolic profile, in vitro bioaccessibility and gut metabolism were assessed. Scanning electron micrographs of the beads with WIBP revealed a relatively rough surface with large pores with craters, but without cracks, which ensures the protection of the encapsulated compounds. X-ray diffraction profiles showed the attenuated of the crystalline peaks, indicating the interactions between alginate and Ca2+. The WIPB antioxidant activity was assessed by FRAP (0.13 mmol Fe2+/g WIBP) and TEAC (0.078 mmol Trolox/g WIBP). The phenolic profile of the craft beer was not altered after the immersion of the beads for 60 days, maintaining its six free phenolic compounds (gallic, 3,4-dihydroxyphenylacetic, 4-hydroxybenzoic, 2,4-dihydroxybenzoic, ferulic, and salicylic acids). The phenolic compounds observed in WIBP and not in the craft beer (quercetin, rutin and syringic acids) were only detected after simulated digestion of WIBP beads that had been immersed in the beer, showing that the encapsulation of WIBP with calcium alginate beads protected the phenolic compounds until consumption. Total phenolic content increased after simulated digestion, and after gut fermentation. During this process the phenolic compounds diversity in each digestion step also increased. Therefore, the enrichment of beer with alginate beads containing the WIBP not only increases the content of phenolic compounds ingested by the consumer, but also the bioaccessibility of those compounds in relation to beer without the beads.